Strengthening Community Mobilization Program: Its Implication on Building Police-Community Relations - Boller-Piol, Annabel A.; Gonzales, Cristina D.; Malapit, Karmela M.; Olivar, Lourdelyn S.; Vega, Alex J.; Villa , Elizabeth B.; Dalugdog, Wilfredo D. (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
This study determined the implications of strengthening community mobilization programs for building police community relations in Batangas Province and utilized a descriptive-quantitative approach with the use of a self-constructed questionnaire based on the parameters of PRO 4A MC No. 2017-02. A total of 392 respondents (15 PCADU personnel and 377 residents from the 13 certified mobilized barangays of Bauan, Batangas) were chosen as the respondents of the study through stratified proportional sampling. The data was gathered two weeks before it was completed and treated with statistical tools such as percentage, weighted mean, and independent t-test. The study revealed that most of the police personnel are Police Corporal, under 5 years in PCADU, and have acquired PCAD Course, Online PCAD Executive Course, and Preparedness Search and Rescue and Relief Operation Seminar. Meanwhile, majority of the community members belong to the middle class, businessman, and live in a rural community. Moreover, the majority of PCADU personnel described CMPs in terms of community organization, community information and education, community empowerment and mobilization, and certification of mobilized barangays as always implemented, with weighted mean of 3.24, 3.23, 3.25, and 3.27, respectively, while the community members described them as often implemented, with weighted mean of 3.18, 3.17, 3.19, and 3.21, respectively. Majority of the respondents strongly agreed on the effects of strengthening CMPs, with weighted mean of 3.29 and 3.23, respectively. The output of the study is a proposed input to help improve the sustainability of CMPs in Batangas Province based on the least-rated items.